1987
DOI: 10.1073/pnas.84.21.7793
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic calcium transients from the beating mammalian heart.

Abstract: To elucidate the role of cytosolic calcium, [Ca2+]1, in the physiology of the normal and ischemic heart, we have developed a method for recording [Ca2+]1 transients from the epicardial surface of the rabbit ventricle after arterial perfusion with the cell-permeant cytosolic calcium indicator indo-l AM. Hearts were illuminated at 360 nm, and fluorescence was recorded simultaneously at 400 and 550 nm. The F4N/F550 fluorescence ratio was calculated by an analog circuit that allowed cancelation of small movement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 34 publications
(21 reference statements)
2
57
2
Order By: Relevance
“…Previous workers have obtained similar findings with both intact ventricular myocardium and isolated ventricular myocytes, and have concluded that this optical phenomenon represents the systolic rise and diastolic fall in [Ca], upon which contraction and relaxation depend (Dubell & Houser, 1987a; Lee et al, 1987;1988). Both the systolic rise in the F400 signal and simultaneous fall in the F500 signal also reflect the rise in [Ca],.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Previous workers have obtained similar findings with both intact ventricular myocardium and isolated ventricular myocytes, and have concluded that this optical phenomenon represents the systolic rise and diastolic fall in [Ca], upon which contraction and relaxation depend (Dubell & Houser, 1987a; Lee et al, 1987;1988). Both the systolic rise in the F400 signal and simultaneous fall in the F500 signal also reflect the rise in [Ca],.…”
Section: Discussionsupporting
confidence: 63%
“…Both the systolic rise in the F400 signal and simultaneous fall in the F500 signal also reflect the rise in [Ca],. However, calculated changes in the ratio of emission intensities at 400 nm and 500 nm respectively were larger than the changes observed in either the F400 or the F500 signal separately, and the ratio has been shown to be less subject to interference and motion artefact (Lee et al, 1987;1988;Eisner et al, 1989). For these reasons the F400/ 500 ratio, rather than its components was used routinely in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors 19,25,26 suggest that the increase in the intracellular calcium is one of the major determinants of the ischemic lesion, through a calcium-dependent mechanism that activates the catabolic enzymes, leading to irreversible damage of the plasmatic membrane, and determining cellular death.…”
Section: Groupmentioning
confidence: 99%